Chitosan/sulfobutylether-β-cyclodextrin nanoparticles as a potential approach for tea polyphenol encapsulation. (June 2016) - Liu, Fei; Antoniou, John; Li, Yue; Majeed, Hamid; Liang, Rong; Ma, Yun; Ma, Jianguo; Zhong, Fang
Abstract: Tea polyphenol (TP)-loaded nanoparticles were formulated by cross-linking chitosan hydrochloride (CSH) and sulfobutyl ether-β-cyclodextrin sodium (SBE-β-CD). Inclusion complexes of TP and SBE-β-CD were initially prepared to effectively encapsulate TP in CSH-SBE-β-CD nanoparticles (CSNs). The stoichiometry of these complexes was determined to be 1:1, using epigallocatechin gallate (EGCG) as a model guest molecule, based on Job's method. The formation of EGCG-SBE-β-CD inclusion complexes was further confirmed by the fluorescence and NMR spectroscopy, and A-ring of EGCG might be included. Prior to the incorporation of TP, the formation conditions of blank CSNs was investigated, ranging from 1.2/1 to 0.75/1 CSH/SBE-β-CD mass ratio. The particle size of TP-loaded CSNs appeared to be increased with decreasing CSH/SBE-β-CD mass ratio from 1.2/1 to 0.75/1, whereas a decreased trend was obtained in the absence of TP. Regardless the presence of TP or not, the particle size increased with increasing CSH concentration. The encapsulation efficiency increased with increasing CSH concentration or decreasing CSH/SBE-β-CD mass ratio while decreased significantly with increasing TP concentration. Cross-linking between CSH and SBE-β-CD was demonstrated with FTIR analysis, and TP was mainly located in the core of CSNs. Atomic force microscopy images showed that TP-loaded CSNs were regular spherical in shape. Results indicate that CSNs can be used as a promising carrier for the encapsulation of water soluble TP. Graphical abstract: Highlights: aInclusion complexes of TP and SBE-β-CD were initially prepared. Inclusion complexes were confirmed using EGCG as the model guest molecule. CSNs could be formed between CSH and SBE-β-CD in the absence of tripolyphosphate. Properties of CSNs could be manipulated by the fabricating parameters.